9x+36-34=

Simple and best practice solution for 9x+36-34= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+36-34= equation:


Simplifying
9x + 36 + -34 = 0

Reorder the terms:
36 + -34 + 9x = 0

Combine like terms: 36 + -34 = 2
2 + 9x = 0

Solving
2 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 9x = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 9x = 0 + -2
9x = 0 + -2

Combine like terms: 0 + -2 = -2
9x = -2

Divide each side by '9'.
x = -0.2222222222

Simplifying
x = -0.2222222222

See similar equations:

| (A^4/b^2c)^5 | | (5x+6)+(3x+23)+(9x+12)=180 | | y=10-10x | | 5x+6+3x+23+9x+12=180 | | 2x+-8y=20 | | 20-4x=7x+53 | | X=50+-4x | | x-.1x=761.20 | | -.428571(m+5)=3+2m | | 112=(4b+8) | | Ix+2I-3x=4 | | 15-0.22x=6.42 | | 5000-x=500+x | | (7x+14)=(3x+6) | | F(3)=(8-3x)(x^2-2x-15) | | 2.5[x+2]+4.5+1.5[x-3]=15 | | X*2-4x=20 | | 7x+2(2x-1)=119 | | 3[x-2]+2[x+1]=-14 | | -(1/7)ln(9) | | 15-3[x-1]=12 | | -3[x+4]+15=-12 | | 6x-4=2x-12 | | 8r+8r(2)=0 | | 1/2(8-x=8-x/2 | | m+(3*.3)=3.5 | | (5r+3r)(r+1)=0 | | 3x+6=5-2x+6 | | 7x+9-2x=10x-12 | | -4(-1)+2y=-30 | | 53=y+1 | | 2x+6+5x+3=51 |

Equations solver categories